Critique as Gift - Bucci, Laura; Diemert, Katherine (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2025)
In our experience, to offer our work up for critique asks us to be vulnerable, and as the critic, to operate from a space of extremes. Drawing from our personal experiences as undergraduate and graduate students (MFA and MAAE) and from the position of a post-secondary teacher and a socially engaged art facilitator, the authors reflect on their research on doing critique as creative process and generous offering. They share their experience in delivering a workshop that explores generative ways of doing critique that include play and embodied methods, and in the process define what critique as gift encompasses.